Bridging Inferences and Learning from Multiple Complementary Texts. Issue 5 (3rd July 2021) - McCrudden, Matthew T.; Huynh, Linh; Lyu, Bailing; Kulikowich, Jonna M.
ABSTRACT: The purpose of this study was to investigate bridging inferences and learning when students with low topic knowledge read multiple complementary biology texts. Using a think-aloud protocol, we assessed students' ( n = 74) cognitive processes while they read one text about principles of natural selection and three texts about examples of natural selection. After reading, participants completed a topic knowledge posttest. Nonparametric tests indicated that readers who had high and moderate scores on the posttest generated more bridges to the principles text than readers who had low scores on the posttest. The multiple regression analysis indicated that bridging inferences to the principles text were predictive of scores on the topic knowledge posttest. An exploratory case analysis highlighted the importance of text-based bridging inferences to principles for readers with the highest scores on the topic knowledge posttest. These findings suggest that starting a set of complementary texts with an overview principles text followed by more exemplar-based texts can support learning when readers with low initial topic knowledge make inferences between principles and examples during reading.